Analysis of Combined Treatment with Azathioprine and Thiotriazoline on the Course of Chronic Liver Disease in Male Rats (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Scope: Hepatotoxicity of medications is an urgent problem all over the world. Such drugs areparticularly dangerous during chronic liver disease. Therefore, today relevant research is devoted to the problemof hepatotoxicity of drugs, and to finding means for its prevention. The purpose of the study was to analyze thecombined effect of azathioprine and thiotriazoline on the course of chronic liver disease with the presence ofhepatocellular insufficiency in male rats. Materials and Methods: For the study, 30 sexually mature white malerats weighing 180–220 g were used, of which the control group consisted of 6 sexually mature white male rats.To model hepatocellular insufficiency, partial hepatectomy was performed. Experimental animals were dividedinto three groups: Groups 1–8 animals, comparison group without treatment, Groups 2–8 animals that receivedazathioprine for 20 days, and Groups 3–8 animals that received azathioprine and thiotriazoline for 20 days; thentheir blood sample was taken for investigation. Results and Discussion: Comparing the results of azathioprinewith those of azathioprine combined with thiotriazoline, significant advantages of combined treatment werefound: Normalization of levels of total bilirubin, total blood protein, cholesterol, a more significant decreasein alanine aminotransferase, and the absence of bone marrow suppression phenomena. Conclusion: Combineduse of thiotriazoline and azathioprine in hepatocellular insufficiency prevents the development of toxic effectsof azathioprine and may be recommended for use in patients with the chronic liver disease. Future studies onthe use of thiotriazoline as a concurrent therapy to protect the liver during treatment with hepatotoxic drugs arerecommended.